OPTIMIZATION OF PREVENTIVE MAINTENANCE AND REPLACEMENT INTERVAL OF CRITICAL COMPONENTS IN THE CUMMINS KTA 38D DIESEL GENERATOR - Wakijo Wakijo; Suparno Suparno; Eko Krisdiono; Anton Nugroho (JOURNAL ASRO, 2022)
The Cummins KTA 38D brand diesel generator is a ship's power generation equipment owned by a supplier to warship electrical needs both at base or in operation. Based on damage report data from 2016 - 2022, the percentage of diesel generator damage reached 38.5% of the total damage to all ship equipment. The results of the analysis using the FTA method cause the failure of the diesel generator to be caused by one of the failure factors in the supporting sub-systems,both from the electrical sub-system, fuel sub-system, air sub-system, fresh water sub-system, seawater sub-system, the lubricant sub-system and the control sub-system were damaged. Calculation using FMECA, there are five critical components based on the RPN value with a "high" risk rating, namely the Body Cover Pump component with the risk of corrosion (205), the Impeller component with the risk of corrosion/cracking (260.5), the Cooler tube component with the risk of leakage (264,7), Mechanical Seal component with risk of damage/leak (192.8), Rectanguler Seal component with risk of leak (196). With a reliability approach and analysis of total cost replacement age preventive maintenance with a minimum reliability limit of 55.84%. It can be proposed maintenance intervals for Body Cover Pump components at 980 running hours with an increase in reliability of 30.87% and maintenance cost savings reaching 14.57%, Impeller components at 1581 running hours with an increase in reliability of 35.79% and maintenance cost savings reaching 29.28%, Cooler tube components at 979 running hours with an increase in reliability of 26.06% and maintenance cost savings reaching 16.40%, mechanical seal components at 1290 running hours with an increase in reliability of 33,20% and savings in maintenance costs reaching 22,57%, the rechtangular seal component on 979 running hours with an increase in reliability of 31.67% and savings in maintenance costs reaching 38.88%. Keywords: FTA, FMECA, Reliability dan Total Cost Replacement Age